2020
DOI: 10.1111/jfpp.14888
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of pea pod powder for formulation of instant pea soup powder

Abstract: Pea (Pisum sativum) family Fabaceae, a common green pod-shaped vegetable is widely grown as a vegetable crop during winter months of October-November. India is the second largest producer of green peas next to China. About 35%-40% of solid waste (green pea peels or pea pods) is generated, after removal of peas from their pods. Pea pods have immense health benefits, as they are an outstanding source of nutrients like vitamins, minerals, and dietary fiber, as well as are low-calorie, low-fat, and cholesterol-fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 26 publications
(45 reference statements)
2
31
0
Order By: Relevance
“…The high viscosity of 15% DGCPp soup may be due to the greater percentage and the functionalities of DGCPp. These findings are consistent with Hanan et al 41 who reported a similar increase in the viscosity of soup pea pod where the peak viscosity of the control soups was 219.7 mPas. Soup samples prepared with DGCPp were more viscous.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…The high viscosity of 15% DGCPp soup may be due to the greater percentage and the functionalities of DGCPp. These findings are consistent with Hanan et al 41 who reported a similar increase in the viscosity of soup pea pod where the peak viscosity of the control soups was 219.7 mPas. Soup samples prepared with DGCPp were more viscous.…”
Section: Resultssupporting
confidence: 92%
“…DGCPp soup (10%) recorded the highest score of the quality attributes among the three DGCPp supplemented soups and was the most highly acceptable one. Similarly, Hanan et al 41 reported that when pea peel powder was increased above 12.5% in the soup formulation, the sensory score of soup decreased. Similarly, Belghith-Fendri et al 42 also found that elevation of pea pod powder above 15% in cake resulted in minimal sensory scores.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Here the pods, or peel of the pea are considered as waste by-products which occupies 55% of the total volume of green peas at the fresh harvested time, the majority of which is disposed as waste and have not generally gained much attention intending to be used (Figure 1). Peapods are agro-industrial by-products emanating from food industries and represents abundant source of natural food bioactive and phenolic antioxidants (Guo et al, 2019;Hanan et al, 2020). Annually in India, peapod waste is discarded in a large amount of almost 1 million ton.…”
Section: Pea Podsmentioning
confidence: 99%
“…For these reasons they have been considered also as a source of dietary fibers (Mateos‐Aparicio et al, 2010a, 2010b). Some scientists studied their possible use in human nutrition by supplementing them in formulating instant soup (Hanan et al, 2020) and in bread enrichment (Belghith Fendri et al, 2016). It also appears that pea pods possess several health benefits, especially antioxidant and anti‐inflammatory activity (Kumari & Deka, 2021).…”
Section: Introductionmentioning
confidence: 99%